Carbon Nanotubes Recent Progress - Muzibur Rahman, Mohammed; Mohamed Asiri, Abdullah (IntechOpen, 2018)
The book Carbon Nanotubes - Recent Progress contains a number of recent researches on synthesis, growth, characterization, development, and potential applications on carbon materials especially CNTs in nanoscale. It is a promising novel research from top to bottom that has received a lot of interest in the last few decades. It covers the advanced topics on the physical, chemical, and potential applications of CNTs. Here, the interesting reports on cutting-edge science and technology related to synthesis, morphology, control, hybridization, and prospective applications of CNTs are concluded. This potentially unique work offers various approaches on the R&D implementation of carbon-related materials and their hybrids. Basically, we know that nanotechnology offers the regulating of substances at the nanoscale and nanodimension substances in few nanometers, in which exclusive phenomenon facilitates us to control the novel practical applications with carbon materials or CNTs. Here, in this book, an overview of current CNTs' fundamental and substantial applications and enactment of the research worldwide is presented. The techniques of CNT preparation, types of carbon material utilization, and possible applications related with CNTs or carbon-hybrid material researches were investigated. It is an important booklet for research organizations, governmental research centers, academic libraries, and R&D affianced in recent research and development of carbon nanotubes.